2001
DOI: 10.1128/jvi.75.22.11218-11221.2001
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Open Reading Frame TRL11/IRL11 Encodes an Immunoglobulin G Fc-Binding Protein

Abstract: Several herpesviruses encode Fc receptors that may play a role in preventing antibody-mediated clearance of the virus in vivo. Human cytomegalovirus (HCMV) induces an Fc-binding activity in cells upon infection, but the gene that encodes this Fc-binding protein has not been identified. Here, we demonstrate that the HCMV AD169 open reading frame TRL11 and its identical copy, IRL11, encode a type I membrane glycoprotein that possesses IgG Fc-binding capabilities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 29 publications
3
50
0
Order By: Relevance
“…In this respect, our findings are reminiscent of effects demonstrated by certain anti-CD45 mAbs showing a differential inhibition of NK cell lysis but not CTL lysis (41). We cannot rule out the possibility that effects on T cells as seen for pUL-11 might require cross-linking of sec49K; however, it should be noted that pUL6, another member of the CMV RL11 family, does not bind CD45 and does not show these effects on T cells (40), and other family members have demonstrated Fc receptor activity (42,43). Thus, differential functions are to be expected from members containing the RL11/CR1 domain.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, our findings are reminiscent of effects demonstrated by certain anti-CD45 mAbs showing a differential inhibition of NK cell lysis but not CTL lysis (41). We cannot rule out the possibility that effects on T cells as seen for pUL-11 might require cross-linking of sec49K; however, it should be noted that pUL6, another member of the CMV RL11 family, does not bind CD45 and does not show these effects on T cells (40), and other family members have demonstrated Fc receptor activity (42,43). Thus, differential functions are to be expected from members containing the RL11/CR1 domain.…”
Section: Discussionmentioning
confidence: 99%
“…Further research using murine monoclonal antibodies directed against the known human IgG Fc receptors revealed that the HCMV-induced Fc receptor was distinct from cellular Fc receptors (MacCormac & Grundy, 1996). Recent studies have shown that the HCMV genome in fact encodes two Fc gamma receptors, one with a molecular mass of 63-68 kDa, encoded by a spliced UL119/UL118 mRNA, and the other with a molecular mass of 34 kDa, encoded by TRL11/IRL11 (Lilley et al, 2001;Atalay et al, 2002). Comparison of the sequences with different cellular Fc receptors suggests that both viral Fc receptors have different ancestors and functions (Atalay et al, 2002).…”
Section: Herpesviridaementioning
confidence: 99%
“…ABB protects virally infected cells from antibodyand complement-dependent neutralization (10), antibody-dependent cell-mediated cytotoxicity (11), and granulocyte attachment (12). The HCMV glycoproteins gp68, gp34, Toll-like receptor 12 (TLR12), and TLR13 act as Fc␥Rs to bind human IgG (3,6,13,14). Recent studies reported formation of ABB complexes with gp68 and with gp34 and demonstrated their functional importance by showing that cells infected with HCMV lacking gp68 and/or gp34 triggered stronger activation of the host Fc␥Rs and NK cells than cells infected with wildtype HCMV (15).…”
mentioning
confidence: 99%
“…HCMV can also establish recurrent secondary infections after reactivation from latency (2). Immune evasion strategies of herpesviruses include expression of viral Fc receptors (Fc␥Rs) that bind host IgG to evade immune responses mediated by host Fc␥Rs (3)(4)(5)(6). Viral Fc␥Rs can participate in antibody bipolar bridging (ABB), whereby an antibody simultaneously binds antigen via its fragment antigen-binding (Fab) arms and an Fc receptor using its Fc (7)(8)(9).…”
mentioning
confidence: 99%